KAJIAN STOK IKAN KERAPU (Cephalopolis sonnerati) BERBASIS HUBUNGAN PANJANG-BERAT YANG DIDARATKAN DITEMPAT PENDARATAN IKAN LHOK PEUKAN BADA, KABUPATEN ACEH BESAR, PROVINSI ACEH - Rika Astuti (Journal of Aceh Aquatic Sciences, 2017)
Grouper is one of fish that has an important economic value and much in demand by the public. The increasing demand for this grouper, then it can cause this type of fish will be subject to arrest, so if this thing continue, this will have a negative impact on the fish population. This study was conducted from February to June 2015 in Lhok Fish Landing Sites Peukan Bada, which includes three Teupin, namely Teupin Ujong Pancu, Lamtengoh, and Lamteh. This study aims to determine the stock grouper (Cephalopolis sonnerati) which covers the length-weight, growth, condition factor, mortality and the rate of exploitation. The primary data such as measurements of total length and weight of grouper, fish dissection. Groupers are measured during the study amounted to 133 long tail with a range of 50-400 mm. Growth coefficient (K) was 0.31 per year with asymptotic length (L∞) of 419.48 mm and the initial theoretical age (t0) amounted to -0.126 per year. Based on the length-weight relationship, it is assumed that the growth pattern grouper (Cephalopolis sonnerati) has a negative allometric, ie the length faster than the fish weight gain. Rated average condition factor is 1.2652, it indicates the fish is still small-sized / thin at the time of the study. Total mortality rate (Z) was 0.73 per year. Natural mortality (M) 0.33 per year, and the mortality rate of arrest (F) 0.40 per year, so that the exploitation rate of 0.55% is obtained. Values exploitation rate has exceeded the optimum exploitation 0.5.Keywords: Groupers, Peukan Bada, growth, mortality, exploitation.